A process for the preparation of tetrakis(dimethylamido)hafnium from hafnium tetrachloride

CN122482950BActive Publication Date: 2026-10-27江西金合新材料有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610953169.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-10-27
Estimated Expiration
2046-06-30

AI Technical Summary

Technical Problem

[0006]本发明针对现有四(二甲氨基)铪制备工艺中转金属化反应耗时过长、产物产率与纯度偏低、工业化经济性差等问题,提供了一种从四氯化铪制备四(二甲氨基)铪的方法

Benefits of technology

[0027]根据本发明的某些优选实施方案,所述金属杂质包括Li+、Na+、Fe3+和Cu2+。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122482950B_ABST
    Figure CN122482950B_ABST
Patent Text Reader

Abstract

The application provides a method for preparing tetrakis(dimethylamido)hafnium from hafnium tetrachloride. The method comprises the following steps: under the condition of water-free, oxygen-free and inert gas protection, cooling an organic solvent to-78 DEG C to-40 DEG C, adding dimethylamine and n-butyl lithium, and stirring to obtain a dimethylamine lithium solution; under the condition of water-free, oxygen-free and inert gas protection, adding hafnium tetrachloride into the dimethylamine lithium solution, adding a palladium-gold composite nanocluster catalyst after uniform stirring, controlling the reaction temperature to be-20 DEG C to 0 DEG C, stirring for 4-5 hours to obtain a reaction liquid; filtering the reaction liquid to remove the precipitate and obtain a filtrate; and sequentially performing normal pressure distillation and reduced pressure rectification on the filtrate to obtain tetrakis(dimethylamido)hafnium. By introducing the palladium-gold composite nanocluster catalyst, the reaction time can be significantly shortened, the product yield and purity can be improved, the side reaction can be inhibited, and the difficulty of separation and purification can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organometallic compound synthesis technology, specifically to the field of high-purity organometallic precursor preparation technology for advanced semiconductor processes, and more specifically, to a method for preparing tetra(dimethylamino)hafnium from hafnium tetrachloride. Background Technology

[0002] With the continuous iteration of microelectronics manufacturing technology, semiconductor devices are constantly evolving towards miniaturization and high density. Traditional silicon dioxide gate dielectrics, due to their low dielectric constant, are prone to problems such as increased gate leakage current and decreased device reliability in advanced nanoscale processes, making them unable to meet the requirements for high-performance chip fabrication. Hafnium oxide, with its high dielectric constant, excellent thermal stability, and silicon substrate compatibility, has become a core alternative material for the gate dielectric layer in advanced logic chips and DRAM memory chips at 14 nm and below. The quality of its thin film directly determines the device performance and lifespan.

[0003] Tetra(dimethylamino)hafnium (TDMAH) is the preferred organometallic precursor for preparing hafnium oxide thin films via atomic layer deposition (ALD) and chemical vapor deposition (CVD) due to its moderate volatility and controllable thermal reactivity. Semiconductor processes have stringent purity requirements for TDMAH; even trace amounts of chlorine impurities, metal ions, or organic byproducts can cause film defects, increased leakage current, and affect device yield. Therefore, developing efficient and high-purity industrial-scale preparation technologies is a key industry requirement.

[0004] Currently, the industrial and laboratory sectors commonly employ a two-step synthetic route using hafnium tetrachloride as the hafnium source and lithium dimethylamino as the amination reagent. Specifically, lithium dimethylamino is first prepared from dimethylamine and n-butyllithium at low temperature, followed by ligand exchange via a transmetallization reaction to generate TDMAH and lithium chloride precipitates. While this route uses readily available raw materials and has a mature reaction pathway, it suffers from significant drawbacks in large-scale production. Firstly, the transmetallization reaction is a nucleophilic substitution process with slow reaction kinetics. Furthermore, the generated lithium chloride easily coats the reactant surface, resulting in extremely long reaction times, long production cycles, low equipment utilization, and high energy consumption and costs. Secondly, the reaction has limited selectivity, easily generating chlorinated intermediate byproducts, leading to low product conversion and yield. Multiple distillations and recrystallizations are required for purification, further increasing production costs. Thirdly, the reaction system is sensitive to water and oxygen, requiring strict anhydrous and oxygen-free protection throughout the process. Controlling existing process conditions is difficult, resulting in insufficient batch stability.

[0005] To address these shortcomings, the industry has attempted various methods, including adjusting the feeding sequence, changing the amination reagent, and introducing microwave or ultrasonic assistance. However, none of these efforts have effectively overcome the core bottlenecks of slow reaction rate and insufficient purity. Some studies have attempted to use conventional catalysts such as palladium black and palladium on carbon, but due to poor dispersion of active sites and insufficient selectivity, the catalytic effect is limited, and metal impurities are easily introduced, reducing product purity and failing to meet the requirements of electronic-grade products. Currently, a dedicated high-efficiency catalyst for the ligand exchange reaction of lithium dimethylamine and hafnium tetrachloride remains a technological gap. Existing processes cannot simultaneously achieve short reaction time, high yield, and ultra-high purity, restricting the stable supply of TDMAH in advanced semiconductor processes. Therefore, developing a novel catalytic synthesis process is of significant practical importance. Summary of the Invention

[0006] This invention addresses the problems of excessively long metallization reaction time, low product yield and purity, and poor industrial economics in existing tetra(dimethylamino)hafnium preparation processes. It provides a method for preparing tetra(dimethylamino)hafnium from hafnium tetrachloride. By introducing a palladium-gold composite nanocluster catalyst, the reaction time is significantly shortened, and the product yield and purity are improved, meeting the stringent requirements of advanced semiconductor processes for electronic-grade products. The technical solution of this invention also simplifies operation, reduces costs, and achieves safe, stable, and industrially scalable high-efficiency preparation, promoting the domestic production and large-scale application of high-purity hafnium-containing precursors.

[0007] Specifically, according to one aspect of the present invention, a method for preparing tetra(dimethylamino)hafnium from hafnium tetrachloride is provided, the method comprising the following steps: (1) Under anhydrous and oxygen-free conditions and inert gas protection, the organic solvent is cooled to -78°C to -40°C, dimethylamine and n-butyllithium are added, and the mixture is stirred to obtain a dimethylamine lithium solution, wherein the organic solvent is n-hexane, cyclohexane, toluene or a mixture thereof, and the molar ratio of dimethylamine to n-butyllithium is in the range of 1:1 to 1.2:1. (2) Under anhydrous and oxygen-free conditions and inert gas protection, hafnium tetrachloride was added to the dimethylaminolithium solution and stirred until homogeneous. Then, palladium-gold composite nanocluster catalyst was added, and the reaction temperature was controlled between -20°C and 0°C. The reaction was stirred for 4-5 hours to obtain a reaction solution, wherein the molar ratio of hafnium tetrachloride to dimethylaminolithium was 1:4.0-1:4.5, and the weight ratio of palladium-gold composite nanocluster catalyst to hafnium tetrachloride was 0.005:1-0.05:1. (3) Filter the reaction solution obtained in step (2) to remove the precipitate and obtain the filtrate; (4) The filtrate obtained in step (3) is subjected to atmospheric distillation to remove the organic solvent, and then the residue is subjected to vacuum distillation to obtain tetra(dimethylamino)hafnium.

[0008] According to certain preferred embodiments of the present invention, the weight ratio of the organic solvent to n-butyllithium is in the range of 100:1 to 200:1.

[0009] According to certain preferred embodiments of the present invention, the n-butyllithium is added in the form of a n-butyllithium solution, the n-butyllithium solution comprising n-butyllithium and an organic solvent, the organic solvent being n-hexane, cyclohexane, toluene, or a mixture thereof.

[0010] According to certain preferred embodiments of the present invention, the concentration of n-butyllithium in the n-butyllithium solution is in the range of 10-25% by weight.

[0011] According to certain preferred embodiments of the present invention, the average particle size of the palladium-gold composite nanocluster catalyst is in the range of 3-12 nm.

[0012] According to certain preferred embodiments of the present invention, the palladium-gold composite nanocluster catalyst is prepared by a method comprising the following steps: (a) Palladium chloride and chloroauric acid are dispersed in a mixed solvent of acetone and water to obtain a mixture, wherein the molar ratio of palladium chloride to chloroauric acid is in the range of 1:8 to 3:8. (b) Add triphenylphosphine to the mixture obtained in step (a) and stir, wherein the ratio of the total number of moles of palladium chloride and chloroauric acid to the number of moles of triphenylphosphine is in the range of 1:1 to 1.2:1; (c) Under the protection of an inert gas, sodium borohydride aqueous solution is added dropwise to the mixture obtained in step (b), and the mixture is stirred at room temperature for 2-4 hours to obtain a palladium-gold composite nanocluster solution; (d) The palladium-gold composite nanocluster solution was centrifuged, washed, and vacuum dried to obtain the palladium-gold composite nanocluster catalyst.

[0013] According to certain preferred embodiments of the present invention, the mixed solvent is a mixture of acetone and water in a volume ratio of 2:1 to 5:1.

[0014] According to certain preferred embodiments of the present invention, in step (a), the total concentration of palladium chloride and chloroauric acid in the mixture is in the range of 10-35 mmol / L.

[0015] According to certain preferred embodiments of the present invention, the concentration of the sodium borohydride aqueous solution is 0.1-0.2 mol / L.

[0016] According to certain preferred embodiments of the present invention, the total molar ratio of palladium chloride and chloroauric acid to the added sodium borohydride is 0.6:1-1.2:1.

[0017] According to certain preferred embodiments of the present invention, in step (a), the molar ratio of palladium chloride to chloroauric acid is in the range of 3:8 to 5:8.

[0018] According to certain preferred embodiments of the present invention, the washing in step (d) includes washing 2-3 times with anhydrous ethanol and then washing 1-2 times with acetone.

[0019] According to certain preferred embodiments of the present invention, the amount of washing solvent used in each washing is 0.5-2 times the volume of the palladium-gold composite nanocluster solution, and the washing method is ultrasonic dispersion followed by centrifugation, with a centrifugation speed of 6000-10000 r / min and a centrifugation time of 15-30 minutes.

[0020] According to certain preferred embodiments of the present invention, the vacuum drying temperature is 50-60°C and the drying time is 5-8 hours.

[0021] According to certain preferred embodiments of the present invention, the temperature of the stirring reaction in step (1) is -60°C to -50°C, and the reaction time is 8-10 hours.

[0022] According to certain preferred embodiments of the present invention, the filtration in step (3) uses a filter membrane with a diameter of 0.22-0.45 μm.

[0023] According to certain preferred embodiments of the present invention, the atmospheric distillation in step (4) is carried out under inert gas protection, the distillation temperature is 40-80°C, and the distillation is stopped when the volume of the distillate is 1 / 5-1 / 3 of the original volume.

[0024] According to certain preferred embodiments of the present invention, the pressure of the vacuum distillation in step (4) is 0.1-1.0 kPa, the temperature of the distillation vessel is 80-120°C, the temperature of the top of the column is 82-95°C, and the reflux ratio is 0.5:1-3:1.

[0025] According to certain preferred embodiments of the present invention, the yield of tetra(dimethylamino)hafnium prepared by the method is above 90%.

[0026] According to certain preferred embodiments of the present invention, the tetra(dimethylamino)hafnium prepared by the method has a metal impurity content of less than 10 ppm and a Cl content of less than 10 ppm. - The content is less than 50 ppm.

[0027] According to certain preferred embodiments of the present invention, the metallic impurity includes Li. + Na + Fe 3+ and Cu 2+ .

[0028] According to certain preferred embodiments of the present invention, the hafnium tetrachloride is in powder form and has a purity of 99.99% or higher.

[0029] Compared with existing technologies, the advantages of this invention are as follows: This invention achieves multiple significant benefits by introducing a specific palladium-gold composite nanocluster catalyst into the metallization reaction. The technical solution of this invention significantly shortens the metallization reaction time, significantly improves production efficiency and equipment utilization, and reduces energy consumption and production costs. The high selectivity of the palladium-gold composite nanocluster catalyst can suppress side reactions, reduce the formation of intermediate by-products, and significantly improve product yield and purity, meeting the stringent requirements of advanced semiconductor processes for electronic-grade purity. This catalyst has good dispersibility, high activity, and can be recycled and reused, further improving economic efficiency. The process conditions of this invention are mild and easy to operate, with strong compatibility with existing industrial routes. Large-scale scaling can be achieved without significant equipment modifications. The reaction process is stable and safe, with good batch consistency, effectively solving the pain points of existing technologies and possessing outstanding industrial application value. Attached Figure Description

[0030] The accompanying drawings are provided in this specification to more clearly explain the technical solutions of the present invention; however, the art is not limited thereto.

[0031] Figure 1 A process flow diagram of a method for preparing tetra(dimethylamino)hafnium from hafnium tetrachloride according to the present invention is shown; Figure 2 A transmission electron microscope (TEM) image of the palladium-gold composite nanocluster catalyst prepared in Preparation Example 1 is shown. Detailed Implementation

[0032] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments. It will be understood that other embodiments may be implemented without departing from the scope or spirit of the invention. Therefore, the following detailed description is non-limiting.

[0033] Unless otherwise specified, all figures used in this specification to represent characteristic dimensions, quantities, and physical properties should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise stated, the numerical parameters listed in the foregoing specification are approximations, and those skilled in the art can appropriately modify these approximations to obtain the desired properties using the teachings disclosed herein.

[0034] As mentioned above, in existing processes for preparing tetra(dimethylamino)hafnium from hafnium tetrachloride, the transfer metallization reaction typically relies on non-catalytic ligand exchange, which suffers from slow reaction kinetics and long processing times, resulting in long production cycles, low equipment utilization, and poor industrial economics. Furthermore, the reaction lacks selectivity, easily generating chlorinated byproducts, and the yield and purity of the product are difficult to meet the electronic-grade standards required for advanced semiconductor processes. Trace amounts of metal and chlorine impurities significantly affect thin film performance. Currently, there is a lack of dedicated, highly efficient catalysts suitable for this ligand exchange reaction, making it impossible to simultaneously meet the requirements of rapid reaction, high yield, ultra-high purity, and large-scale production. This invention aims to solve the above problems.

[0035] Specifically, the present invention provides a method for preparing tetra(dimethylamino)hafnium from hafnium tetrachloride. Figure 1 A process flow diagram of a method for preparing tetra(dimethylamino)hafnium from hafnium tetrachloride according to the present invention is shown, including: (1) Under anhydrous and oxygen-free conditions and inert gas protection, the organic solvent is cooled to -78°C to -40°C, dimethylamine and n-butyllithium are added, and the mixture is stirred to obtain a dimethylamine lithium solution. (2) Under anhydrous and oxygen-free conditions and inert gas protection, hafnium tetrachloride was added to a lithium dimethylamine solution and stirred until homogeneous. Then palladium-gold composite nanocluster catalyst was added, and the reaction temperature was controlled between -20°C and 0°C. The reaction was stirred for 4-5 hours to obtain the reaction solution. (3) Filter the reaction solution to remove the precipitate and obtain the filtrate; (4) The filtrate was subjected to atmospheric distillation and vacuum distillation in sequence to obtain tetra(dimethylamino)hafnium.

[0036] Specifically, according to one aspect of the present invention, a method for preparing tetra(dimethylamino)hafnium from hafnium tetrachloride is provided, the method comprising the following steps: (1) Under anhydrous and oxygen-free conditions and inert gas protection, the organic solvent is cooled to -78°C to -40°C, dimethylamine and n-butyllithium are added, and the mixture is stirred to obtain a dimethylamine lithium solution, wherein the organic solvent is n-hexane, cyclohexane, toluene or a mixture thereof, and the molar ratio of dimethylamine to n-butyllithium is in the range of 1:1 to 1.2:1. (2) Under anhydrous and oxygen-free conditions and inert gas protection, hafnium tetrachloride was added to the dimethylaminolithium solution and stirred until homogeneous. Then, palladium-gold composite nanocluster catalyst was added, and the reaction temperature was controlled between -20°C and 0°C. The reaction was stirred for 4-5 hours to obtain a reaction solution, wherein the molar ratio of hafnium tetrachloride to dimethylaminolithium was 1:4.0-1:4.5, and the weight ratio of palladium-gold composite nanocluster catalyst to hafnium tetrachloride was 0.005:1-0.05:1. (3) Filter the reaction solution obtained in step (2) to remove the precipitate and obtain the filtrate; (4) The filtrate obtained in step (3) is subjected to atmospheric distillation to remove the organic solvent, and then the residue is subjected to vacuum distillation to obtain tetra(dimethylamino)hafnium.

[0037] The method described in this invention uses hafnium tetrachloride as the hafnium source and lithium dimethylamino as the amination reagent. It achieves efficient, selective, and high-purity synthesis of tetra(dimethylamino)hafnium by introducing a palladium-gold composite nanocluster catalyst. This method overcomes the technical bottlenecks of traditional preparation processes, such as slow reaction kinetics, low product yield, difficulty in controlling impurity content, and excessively long production cycles. It can meet the stringent purity and stability requirements of advanced semiconductor processes for electronic-grade organometallic precursors. Specifically, the reaction system of this invention is carried out entirely under anhydrous and oxygen-free conditions with inert gas protection. This effectively prevents the decomposition, oxidation, or generation of hydroxyl or oxygen-bridged byproducts from contact with water or oxygen, ensuring reaction stability and product purity. Preferably, the inert gas used is high-purity nitrogen or argon with a purity of not less than 99.999%. The reaction apparatus undergoes multiple vacuuming and inert gas purging cycles to ensure that the moisture and oxygen content in the system are both below 10 ppm, matching the environmental requirements for electronic-grade product preparation.

[0038] According to the technical solution of the present invention, step (1) is a deprotonation reaction of dimethylamine and n-butyllithium to generate strongly nucleophilic dimethylaminolithium, which serves as the amino source for subsequent ligand exchange reactions. This reaction is a strongly exothermic and rapid proton transfer process, and therefore it is preferably carried out in a low-temperature, inert atmosphere, and an anhydrous organic solvent system to prevent hydrolysis and deactivation of n-butyllithium and the occurrence of side reactions.

[0039] According to the technical solution of the present invention, the organic solvent selected in step (1) is n-hexane, cyclohexane, toluene, or a mixture thereof. All of the above solvents are anhydrous aprotic inert solvents, possessing high chemical stability, not reacting with n-butyllithium, dimethylaminolithium, hafnium tetrachloride, or the target product, and exhibiting good low-temperature fluidity, maintaining a homogeneous liquid phase between -78℃ and -40℃ to ensure mass transfer efficiency and a suitable boiling point, thus facilitating subsequent atmospheric distillation for removal.

[0040] According to certain preferred embodiments of the present invention, the weight ratio of the organic solvent to n-butyllithium is in the range of 100:1 to 200:1.

[0041] According to the technical solution of the present invention, the molar ratio of dimethylamine to n-butyllithium in step (1) is in the range of 1:1 to 1.2:1. Insufficient or equal molar ratios of n-butyllithium will lead to incomplete conversion of dimethylamine, reducing the effective concentration of the amino source; excessive n-butyllithium will easily trigger side reactions and introduce lithium ion impurities, increasing the difficulty of subsequent separation and purification. A molar ratio of 1.0-1.2 times ensures that dimethylamine and n-butyllithium are essentially completely converted to dimethylaminolithium.

[0042] According to certain preferred embodiments of the present invention, the n-butyllithium is added in the form of a n-butyllithium solution. The n-butyllithium solution comprises n-butyllithium and an organic solvent, wherein the organic solvent is n-hexane, cyclohexane, toluene, or a mixture thereof. Preferably, the concentration of n-butyllithium in the n-butyllithium solution is in the range of 10-25% by weight. Solution-based addition provides more uniform feeding and higher safety, avoiding the risk of localized violent reactions caused by direct solid feeding.

[0043] According to the technical solution of the present invention, in step (1), the organic solvent is cooled to -78°C to -40°C, preferably -60°C to -50°C. The reaction is stirred at this temperature for 8-10 hours. Low temperature conditions can effectively suppress side reactions, prevent dimethylamine volatilization, and stabilize the dimethylamine lithium structure. Excessively high temperatures can easily lead to the decomposition of n-butyllithium, dimethylamine escape, and a reduction in the yield of aminolithium; excessively low temperatures increase energy consumption and reduce the reaction rate.

[0044] Step (2) of this invention is a transmetallization ligand exchange reaction of hafnium tetrachloride and dimethylaminolithium. In traditional processes, this reaction is a non-catalyzed nucleophilic substitution reaction, which suffers from slow reaction kinetics, easy coating of reactants by lithium chloride precipitate, numerous side reactions, and reaction times exceeding 20 hours (or even 25 hours). This invention, by introducing a palladium-gold composite nanocluster catalyst, simultaneously achieves a significant improvement in reaction rate, reaction selectivity, and product yield.

[0045] Specifically, according to the technical solution of the present invention, the molar ratio of hafnium tetrachloride to lithium dimethylamine in step (2) is 1:4.0-1:4.5. Preferably, the catalytic reaction temperature in step (2) is between -20°C and 0°C, and the reaction is stirred for 4-5 hours. Low temperature conditions can inhibit the thermal decomposition of the target product and reduce the occurrence of side reactions. Too high a temperature can easily lead to product decomposition and aggravate side reactions, while too low a temperature will reduce catalytic activity and prolong the reaction time. Under the action of palladium-gold composite nanocluster catalyst, the reaction time can be significantly shortened from more than 20 hours in the traditional process to less than 5 hours, and the production efficiency is increased by more than 80%, thereby significantly improving the equipment utilization rate.

[0046] Preferably, in step (2), the weight ratio of palladium-gold composite nanocluster catalyst to hafnium tetrachloride is 0.005:1-0.05:1. Too low a catalyst dosage will result in insufficient catalytic effect, while too high a dosage will increase production costs and the risk of introducing metal impurities. The above dosage range can achieve highly efficient catalysis while ensuring that the metal impurity content in the product is below 10 ppm, meeting the requirements for electronic-grade products.

[0047] According to certain preferred embodiments of the present invention, the average particle size of the palladium-gold composite nanocluster catalyst is in the range of 3-12 nm. This particle size range allows the catalyst to possess both high specific surface area and structural stability. If the particle size is too small, agglomeration and deactivation are likely to occur, while if the particle size is too large, the specific surface area will be too low and the active sites will be insufficient.

[0048] According to an embodiment of the present invention, the palladium-gold composite nanocluster catalyst can be prepared by liquid-phase reduction method with reference to relevant prior art. For example, the specific preparation steps of the palladium-gold composite nanocluster catalyst include: (a) Palladium chloride and chloroauric acid are dispersed in a mixed solvent of acetone and water to obtain a mixture, wherein the molar ratio of palladium chloride to chloroauric acid is in the range of 1:8-6:8, preferably 3:8-5:8, the mixed solvent is a mixture of acetone and water in a volume ratio of 2:1-5:1, and the total concentration of palladium chloride and chloroauric acid in the mixture is in the range of 10-35 mmol / L; (b) Add triphenylphosphine to the mixture obtained in step (a) and stir, wherein the ratio of the total number of moles of palladium chloride and chloroauric acid to the number of moles of triphenylphosphine is in the range of 1:1 to 1.2:1; (c) Under the protection of an inert gas, sodium borohydride aqueous solution is added dropwise to the mixture obtained in step (b), and the mixture is stirred at room temperature for 2-4 hours to obtain a palladium-gold composite nanocluster solution.

[0049] (d) The palladium-gold composite nanocluster solution is centrifuged, washed, and vacuum dried to obtain the palladium-gold composite nanocluster catalyst. The centrifugation speed is preferably 6000-10000 r / min, and the centrifugation time is 15-30 minutes. The washing includes washing with anhydrous ethanol 2-3 times and then washing with acetone 1-2 times. The amount of washing solvent used in each washing is 0.5-2 times the volume of the palladium-gold composite nanocluster solution. The washing method is ultrasonic dispersion followed by centrifugation. The vacuum drying temperature is 50-60℃, and the drying time is 5-8 hours.

[0050] Preferably, the concentration of the sodium borohydride aqueous solution is 0.1-0.2 mol / L, and the molar ratio of the total number of moles of palladium chloride and chloroauric acid to the added sodium borohydride is 0.6:1-1.2:1.

[0051] The core innovation of this palladium-gold composite nanocluster catalyst lies in the bimetallic synergistic catalytic effect, the specific mechanism of which is as follows: there is a significant electron transfer and synergistic regulation between palladium and gold. Specifically, the Fermi level of gold is higher than that of palladium, and electrons are transferred from gold to palladium, making the palladium sites electron-rich and the gold sites electron-deficient, forming complementary electronic active centers. The electron-rich palladium sites can enhance the activation ability of the hafnium-chlorine (Hf-Cl) bond in hafnium tetrachloride, weakening the hafnium-chlorine bond through electron feedback, thereby lowering the chloride ion leaving energy barrier. On the other hand, the electron-deficient gold sites can enhance the adsorption and activation of dimethylamino groups in dimethylaminolithium, increasing the nucleophilic activity of the amino group, thereby accelerating the nucleophilic attack of the amino group on the hafnium center. This synergistic effect significantly reduces the activation energy of the ligand exchange reaction and increases the reaction rate constant by more than an order of magnitude, thereby significantly shortening the reaction time. At the same time, the nano-size of the nanocluster endows the catalyst with a large specific surface area and abundant edge defect active sites. The high specific surface area provides ample contact and activation interfaces for reactants, exhibiting specific catalytic activity for hafnium-chlorine bond breaking and nitrogen-hafnium bond formation. Furthermore, this catalyst achieves precise catalysis through steric hindrance and electron selectivity; the bimetallic center precisely controls the reaction pathway, guiding the gradual substitution of chlorine atoms by dimethylamino groups until tetrasubstituted completion, reducing the accumulation of chlorinated intermediates. Additionally, in conventional processes, lithium chloride precipitates easily coat reactants, leading to reaction termination. The catalyst of this invention, with its surface modified by triphenylphosphine, possesses hydrophobic and anti-adsorption properties, reducing the adsorption and coating of lithium chloride precipitates on the catalyst and reactant surfaces. The bimetallic nanocluster structure of this invention is stable, and metal ions are not easily dissolved during catalysis. The total content of metal impurities such as lithium ions, sodium ions, iron ions, and copper ions in the product is less than 10 ppm, thus meeting the stringent requirements of advanced semiconductor processes for electronic-grade precursors.

[0052] According to the technical solution of the present invention, in step (3), the reaction solution is filtered to remove lithium chloride precipitate and part of the catalyst solid, resulting in a clear filtrate containing the target product. Preferably, a 0.22-0.45 μm filter membrane is used for filtration, which can efficiently retain solid particles. Preferably, the filtration process is carried out under inert gas protection to avoid the filtrate from contacting water and oxygen, which could lead to product degradation.

[0053] According to the technical solution of the present invention, in step (4), the filtrate is subjected to atmospheric distillation and vacuum distillation in sequence to achieve two-stage purification. Specifically, atmospheric distillation is carried out under the protection of an inert gas, the distillation temperature is 40-80℃, and distillation is stopped when the volume of the fraction is 1 / 5-1 / 3 of the original volume, which can remove most of the organic solvent and low-boiling point impurities and avoid high-boiling point impurities from contaminating the distillation column.

[0054] According to the technical solution of the present invention, the pressure of vacuum distillation is 0.1-1.0 kPa, the temperature of the distillation vessel is 80-120℃, the temperature of the top of the column is 82-95℃, and the reflux ratio is 0.5:1-3:1. High vacuum conditions can lower the boiling point of the product and avoid high-temperature decomposition. Precise control of the temperature and reflux ratio enables efficient separation of the target product from residual solvents and byproducts, yielding electronic-grade tetra(dimethylamino)hafnium with a purity of over 99.994%.

[0055] According to a preferred embodiment of the present invention, the bimetallic synergistic effect is optimal when the molar ratio of palladium chloride to chloroauric acid is 3:8-5:8, resulting in the best catalytic activity and selectivity. Furthermore, the reaction temperature in step (1) is preferably -60°C to -50°C, and the reaction temperature in step (2) is preferably -20°C to -10°C, which balances reaction rate, selectivity, and product stability, further reducing byproduct formation. Preferably, the vacuum distillation pressure is 0.1-0.5 kPa, and the reflux ratio is preferably 1:1-2:1.

[0056] The technical solution of the present invention is simple to operate, highly compatible with existing industrial routes, requires no major modification to production equipment, exhibits significant bimetallic synergistic effect of catalyst, high activity, good selectivity, and recyclability, further reducing industrial production costs. It can achieve rapid, high-yield, high-purity, and large-scale preparation of tetra(dimethylamino)hafnium, providing high-quality organometallic precursors for advanced semiconductor processes, and has significant technical value and broad industrial application prospects.

[0057] The present invention will now be described in more detail with reference to embodiments. It should be noted that these descriptions and embodiments are intended to facilitate understanding of the present invention and are not intended to limit the invention.

[0058] Example In this invention, unless otherwise specified, the "%" refers to "weight %" and the "parts" refers to "parts by weight".

[0059] Table 1 below lists specific information about the raw materials used in the embodiments and comparative examples of the present invention.

[0060] Table 1 List of Experimental Materials

[0061] Table 2 below lists specific information about the experimental equipment used in the embodiments and comparative examples of the present invention.

[0062] Table 2 List of Experimental Equipment

[0063] Test methods (a) Yield The yields of the tetra(dimethylamino)hafnium products prepared in the following examples and comparative examples were determined according to the methods described below.

[0064] The yield calculation is based on hafnium tetrachloride. According to the stoichiometric ratio of the reaction and the actual mass of pure tetra(dimethylamino)hafnium obtained, the actual yield of the product is calculated using the following formula: Yield (%) = [Actual mass of pure tetra(dimethylamino)hafnium (g)] / [Mass of hafnium tetrachloride feedstock (g) × Purity of hafnium tetrachloride feedstock (%) × (Molar mass of tetra(dimethylamino)hafnium (370.82 g / mol) / Molar mass of hafnium tetrachloride (320.30 g / mol))] × 100% The testing steps are as follows: 1. Accurately weigh the mass of hafnium tetrachloride feedstock used in the reaction (accurate to 0.0001 g); 2. The mass of pure tetra(dimethylamino)hafnium obtained by weighing in a glove box filled with high-purity inert gas (water and oxygen content both less than 1 ppm). Specifically, the product was transferred to a pre-dried, constant-weight weighing bottle using the difference method, and weighed accurately (to 0.0001 g). The mass was obtained by the difference in mass before and after weighing. 3. Substitute the values ​​into the above formula to calculate the yield. Perform the test in parallel three times and take the average value as the final yield data.

[0065] (II) Cl - Content testing The Cl content in the product was tested using an automatic potentiometric titrator. - The content was determined using a Metrohm 902 Titrando instrument and argentometric titration. The specific test steps are as follows: 1. Reagent preparation: Prepare a 0.01 mol / L silver nitrate standard titration solution (prepared from standard silver nitrate reagent and standardized); prepare a nitric acid solution (1:1, volume ratio, analytical grade); use high-purity water (resistivity ≥18.2 MΩ•cm) for the experiment.

[0066] 2. Sample Preparation: In a fume hood, accurately weigh 5g of the sample to be tested (accurate to 0.0001g, denoted as m) and place it in a 250mL beaker. Slowly add 20mL of high-purity water, then add 5mL of nitric acid solution (1:1). Gently heat (40-50℃) and stir to ensure complete hydrolysis of the sample (tetra(dimethylamino)hafnium hydrolyzes to produce hydrogen chloride and dimethylamine, with the dimethylamine escaping). Cool to room temperature, quantitatively transfer the hydrolysate to a 100mL volumetric flask, dilute to the mark with high-purity water, and mix well to obtain the sample solution.

[0067] 3. Titration Test: Accurately transfer 50 mL of sample solution into a titration vessel, insert the electrode, and perform potentiometric titration with silver nitrate standard titration solution (concentration denoted as c, unit mol / L) while stirring. Record the volume V (unit mL) consumed at the titration endpoint. Simultaneously, perform the same titration with 50 mL of blank solution (prepared by replacing the sample with an equal volume of high-purity water and nitric acid solution, following the same hydrolysis and volume adjustment steps), and record the blank consumption volume V0.

[0068] 4. Calculation: Based on the concentration, volume consumed, and sample mass of the silver nitrate standard titration solution, calculate the Cl content in the sample. - The content (unit: ppm) is calculated using the following formula:

[0069] Where V is the volume (mL) of silver nitrate standard titration solution consumed by the sample solution; V0 is the volume (mL) of silver nitrate standard titration solution consumed by the blank solution; c is the concentration (mol / L) of the silver nitrate standard titration solution; 35.45 is the concentration of Cl. - The molar mass (g / mol); 100 / 50 is the ratio of the fixed volume to the transferred volume (volume correction factor); m is the sample mass (g).

[0070] The test was performed in parallel three times, and the average value was taken as the final Cl. - content.

[0071] (III) Purity The purity of the tetra(dimethylamino)hafnium products prepared in the following examples and comparative examples was determined using trace metal analysis. Specifically, the total content of metal impurities in the tetra(dimethylamino)hafnium products prepared in the following examples and comparative examples was determined by inductively coupled plasma mass spectrometry, supplemented by chloride ion content and moisture content test results. The final purity of the product was calculated by the difference method. The purity calculation formula is as follows: Purity of tetra(dimethylamino)hafnium (%) = 100% - (Total metal impurities (ppm) + Cl) - Content (ppm) + Moisture content (ppm) / 10000 The specific testing steps are as follows: In an anhydrous and oxygen-free glove box, weigh 1.0 g of tetrakis(dimethylamino)hafnium sample and place it in an acid-washed PFA digestion vessel. Slowly add 5 mL of high-purity concentrated nitric acid and 2 mL of high-purity hydrogen peroxide (30%), seal the vessel, and place it in a microwave digester. Digest at 120°C for 30 minutes to ensure complete conversion of the sample to the inorganic state. After digestion, cool the vessel and bring the volume to 50 mL with 2% dilute nitric acid. Simultaneously prepare a reagent blank solution without the sample.

[0072] The determination was performed using inductively coupled plasma mass spectrometry (iCAP Q). A standard addition method was used to prepare the standard curve solution to eliminate the matrix effect of high-concentration hafnium matrix on the determination of trace metal elements. The concentrations of 22 trace metal elements, including Li, Na, Mg, Al, K, Ca, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Mo, Ag, Cd, Sn, Ba, Pt, Au, and Pb, were simultaneously determined in the sample solution in collisional reaction cell mode (KED, using helium as the reactant gas).

[0073] The concentration of each metal element in the sample solution is calculated based on the standard curve, and then converted to the metal impurity content in the sample (unit: ppm) using the following formula: Metal impurity content (ppm) = (C × V) / m × 1000 Where C is the mass concentration (μg / L) of the metal element to be tested in the sample solution after deducting the reagent blank, V is the final volume (mL), and m is the sample mass (g). The total metal impurity content is the sum of the measured values ​​of the above 22 elements.

[0074] Moisture content was determined using a Karl Fischer coulometric moisture analyzer, and chloride ion content was determined using an automatic potentiometric titrator. The measured total metal impurity content and Cl... - Substituting the content and moisture content into the purity calculation formula, the purity of tetra(dimethylamino)hafnium was obtained. Three parallel tests were performed, and the average value was taken as the final purity. The results are recorded in Table 4.

[0075] (iv) Reaction time recording According to the disclosure of this invention, the reaction time specifically refers to the catalytic reaction stage of hafnium tetrachloride and dimethylaminolithium under the action of a catalyst, and the specific recording method is as follows: 1. Timing begins after hafnium tetrachloride is added, catalyst is added, and the reactor is sealed; 2. Maintain stable process parameters such as reaction temperature and stirring speed, and take samples every 30 minutes to test the content of tetrakis(dimethylamino)hafnium in the samples by GC-MS; 3. When the content of tetra(dimethylamino)hafnium in the sample no longer increases significantly (change ≤ 0.1% / h), stop timing. The time recorded at this time is the reaction time.

[0076] The reaction time was recorded three times for each sample, and the average value was taken as the final reaction time.

[0077] Preparation Example 1: Preparation of Palladium-Gold Composite Nanocluster Catalyst 1 The specific steps for preparing Example 1 are as follows: (1) Preparation of the mixture: In an anhydrous and oxygen-free glove box (moisture content ≤10 ppm, oxygen content ≤10 ppm), take 0.1 mmol palladium chloride and 0.8 mmol chloroauric acid, add them to 50 mL of a mixture of acetone and deionized water with a volume ratio of 2:1, place it in an ultrasonic disperser, and ultrasonically disperse it at 400 W for 20 minutes until the solid is completely dissolved to obtain a uniform and transparent mixture.

[0078] (2) Ligand addition and stirring: Slowly add 0.9 mmol of triphenylphosphine to the above mixture, start the magnetic stirrer, and stir at 300 rpm at room temperature for 30 minutes.

[0079] (3) Reduction reaction: The mixture was transferred to a three-necked flask equipped with an inert gas protection device, and high-purity nitrogen (99.999%) was introduced and continuously purged for 30 minutes. Subsequently, a 0.1 mol / L sodium borohydride aqueous solution was slowly added dropwise using a constant-pressure dropping funnel at a dropping rate of 1 mL / min. After the addition was complete, the reaction was continued to be stirred at room temperature for 3 hours. During this period, the solution color gradually changed from light yellow to dark brown, and finally a homogeneous palladium-gold composite nanocluster solution was obtained; wherein the total molar ratio of palladium chloride and chloroauric acid to sodium borohydride was 0.9:1.5.

[0080] (4) Centrifugation, washing, and drying: The above palladium-gold composite nanocluster solution was transferred to a high-speed centrifuge tube, centrifuged at 8000 r / min for 20 minutes, and the bottom precipitate was collected. The precipitate was first ultrasonically dispersed and washed twice with 50 mL of anhydrous ethanol, each time for 10 minutes, followed by centrifugation. Then, it was ultrasonically dispersed and washed once with 25 mL of acetone, followed by centrifugation. The volume of solvent used for each wash was equal to the volume of the palladium-gold composite nanocluster solution. The washed precipitate was transferred to a vacuum drying oven and dried at 55℃ and a vacuum of -0.095 MPa for 6 hours to obtain a dark brown powdery palladium-gold composite nanocluster catalyst 1.

[0081] Figure 2 A transmission electron microscope (TEM) image of the palladium-gold composite nanocluster catalyst 1 prepared in Preparation Example 1 is shown. Figure 2 As shown, the palladium-gold composite nanocluster catalyst 1 exhibits a uniform, spherical particle distribution. TEM analysis revealed that the average particle size of this catalyst is approximately 6 nm.

[0082] Preparation Example 2: Preparation of Palladium-Gold Composite Nanocluster Catalyst 2 The specific steps for preparing Example 2 are as follows: (1) Preparation of the mixture: In an anhydrous and oxygen-free glove box, take 0.2 mmol of palladium chloride and 0.8 mmol of chloroauric acid and add them to 50 mL of a mixture of acetone and deionized water with a volume ratio of 3:1. Disperse the mixture by ultrasonication at 400 W for 20 minutes to obtain a uniform and transparent mixture.

[0083] (2) Ligand addition and stirring: 1.1 mmol of triphenylphosphine was slowly added to the mixture and stirred at 300 rpm at room temperature for 30 minutes.

[0084] (3) Reduction reaction: The mixture was transferred to a three-necked flask, and high-purity nitrogen was introduced to remove air and moisture. Then, a sodium borohydride aqueous solution with a concentration of 0.15 mol / L was slowly added dropwise at a rate of 1 mL / min. After the addition was completed, the mixture was stirred at room temperature for 3 hours to obtain a dark brown palladium-gold composite nanocluster solution. The total molar ratio of palladium chloride and chloroauric acid to sodium borohydride was 1.0:1.6.

[0085] (4) Centrifugation, washing, and drying: The nanocluster solution was centrifuged at 8000 r / min for 20 minutes, and the precipitate was collected. It was first ultrasonically washed twice with 50 mL of anhydrous ethanol, and then ultrasonically washed once with 25 mL of acetone, centrifuged after each washing. The precipitate was placed in a vacuum drying oven and dried at 55 °C and a vacuum of -0.095 MPa for 6 hours to obtain a dark brown powdery palladium-gold composite nanocluster catalyst 2. TEM analysis showed that this catalyst had a similar morphology to the palladium-gold composite nanocluster catalyst prepared in Preparation Example 1, with an average particle size of approximately 7 nm.

[0086] Preparation Example 3: Preparation of Palladium-Gold Composite Nanocluster Catalyst 3 The specific steps for preparing Example 3 are as follows: (1) Preparation of the mixture: In an anhydrous and oxygen-free glove box, take 0.3 mmol of palladium chloride and 0.8 mmol of chloroauric acid and add them to 50 mL of a mixed solvent of acetone and deionized water with a volume ratio of 5:1. Disperse the mixture by ultrasonication at 400 W for 20 minutes to obtain a uniform and transparent mixture.

[0087] (2) Ligand addition and stirring: 1.32 mmol of triphenylphosphine was slowly added to the mixture and stirred at 300 rpm at room temperature for 30 minutes.

[0088] (3) Reduction reaction: The mixture was transferred to a three-necked flask, and high-purity nitrogen was introduced to remove air and moisture. Then, a sodium borohydride aqueous solution with a concentration of 0.2 mol / L was slowly added dropwise at a rate of 1 mL / min. After the addition was completed, the mixture was stirred at room temperature for 3 hours to obtain a dark brown palladium-gold composite nanocluster solution. The molar ratio of the total number of moles of palladium chloride and chloroauric acid to sodium borohydride was 1.1:1.8.

[0089] (4) Centrifugation, washing, and drying: The nanocluster solution was centrifuged at 8000 r / min for 20 minutes, and the precipitate was collected. It was first ultrasonically washed three times with 50 mL of anhydrous ethanol, and then ultrasonically washed twice with 25 mL of acetone. Centrifugation was performed after each washing, with the amount of solvent used being 1.5 times the volume of the palladium-gold composite nanocluster solution. The precipitate was placed in a vacuum drying oven and dried at 55 °C and a vacuum of -0.095 MPa for 6 hours to obtain a dark brown powder of palladium-gold composite nanocluster catalyst 3. TEM analysis showed that this catalyst had a similar morphology to the palladium-gold composite nanocluster catalyst prepared in Preparation Example 1, with an average particle size of approximately 9 nm.

[0090] Preparation Example 4: Preparation of Palladium-Gold Composite Nanocluster Catalyst 4 The specific steps for preparing Example 4 are as follows: (1) Preparation of the mixture: In an anhydrous and oxygen-free glove box, take 0.4 mmol of palladium chloride and 0.8 mmol of chloroauric acid and add them to 50 mL of a mixed solvent of acetone and deionized water with a volume ratio of 2:1. Disperse the mixture by ultrasonication at 400 W for 20 minutes to obtain a uniform and transparent mixture.

[0091] (2) Ligand addition and stirring: 1.1 mmol of triphenylphosphine was slowly added to the mixture and stirred at 300 rpm at room temperature for 30 minutes.

[0092] (3) Reduction reaction: The mixture was transferred to a three-necked flask, and high-purity nitrogen was introduced to remove air and moisture. Then, a sodium borohydride aqueous solution with a concentration of 0.1 mol / L was slowly added dropwise at a rate of 1 mL / min. After the addition was completed, the mixture was stirred at room temperature for 3 hours to obtain a dark brown palladium-gold composite nanocluster solution. The molar ratio of the total number of moles of palladium chloride and chloroauric acid to sodium borohydride was 1.2:2.0.

[0093] (4) Centrifugation, washing, and drying: The nanocluster solution was centrifuged at 8000 r / min for 20 minutes, and the precipitate was collected. It was first ultrasonically washed twice with 50 mL of anhydrous ethanol, and then ultrasonically washed once with 25 mL of acetone, centrifuged after each washing. The precipitate was placed in a vacuum drying oven and dried at 55 °C and a vacuum of -0.095 MPa for 6 hours to obtain a dark brown powdery palladium-gold composite nanocluster catalyst 4. TEM analysis showed that this catalyst had a similar morphology to the palladium-gold composite nanocluster catalyst prepared in Preparation Example 1, with an average particle size of approximately 6 nm.

[0094] Preparation Example 5: Preparation of Palladium Nanocluster Catalysts The specific steps for preparing Example 5 are as follows: (1) Preparation of the mixture: In an anhydrous and oxygen-free glove box, take 0.9 mmol of palladium chloride and add it to 50 mL of a mixed solvent of acetone and deionized water with a volume ratio of 2:1. Disperse the mixture with ultrasonic power of 400 W for 20 minutes until the solid is completely dissolved to obtain a uniform and transparent palladium chloride solution.

[0095] (2) Ligand addition and stirring: Slowly add 0.9 mmol of triphenylphosphine to the above palladium chloride solution, start the magnetic stirrer, and stir at 300 rpm at room temperature for 30 minutes.

[0096] (3) Reduction reaction: The solution was transferred to a three-necked flask with an inert gas protection device, and high-purity nitrogen was introduced for 30 minutes to remove air and moisture from the system, while maintaining a continuous nitrogen flow. Subsequently, a 0.1 mol / L sodium borohydride aqueous solution was slowly added dropwise using a constant pressure dropping funnel at a dropping rate of 1 mL / min. After the addition was complete, the reaction was continued to be stirred at room temperature for 3 hours. During this period, the solution color gradually changed from pale yellow to black, and finally a uniform palladium nanocluster solution was obtained; wherein, the molar ratio of palladium chloride to sodium borohydride was 0.9:1.5.

[0097] (4) Centrifugation, washing, and drying: The palladium nanocluster solution was transferred to a high-speed centrifuge tube, centrifuged at 8000 r / min for 20 minutes, and the black precipitate at the bottom was collected. The precipitate was first ultrasonically dispersed and washed twice with 50 mL of anhydrous ethanol, each time for 10 minutes, followed by centrifugation. Then, it was ultrasonically dispersed and washed once with 25 mL of acetone, followed by centrifugation. The washed precipitate was transferred to a vacuum drying oven and dried at 55℃ and a vacuum of -0.095 MPa for 6 hours to obtain a black powdered palladium nanocluster catalyst. TEM analysis showed that the average particle size of the catalyst was approximately 8 nm.

[0098] Preparation Example 6: Preparation of Gold Nanocluster Catalysts The specific steps for preparing Example 6 are as follows: (1) Preparation of the mixture: In an anhydrous and oxygen-free glove box, take 0.9 mmol of chloroauric acid and add it to 50 mL of a mixture of acetone and deionized water with a volume ratio of 2:1. Disperse the mixture with ultrasonic power of 400 W for 20 minutes until the solid is completely dissolved to obtain a uniform and transparent chloroauric acid solution.

[0099] (2) Ligand addition and stirring: Slowly add 0.9 mmol of triphenylphosphine to the above chloroauric acid solution, start the magnetic stirrer, and stir at 300 rpm at room temperature for 30 minutes.

[0100] (3) Reduction reaction: The solution was transferred to a three-necked flask with an inert gas protection device, and high-purity nitrogen was introduced for 30 minutes to remove air and moisture from the system, while maintaining a continuous nitrogen flow. Subsequently, a 0.1 mol / L sodium borohydride aqueous solution was slowly added dropwise using a constant pressure dropping funnel at a dropping rate of 1 mL / min. After the addition was complete, the reaction was continued to be stirred at room temperature for 3 hours. During this period, the solution color gradually changed from yellow to dark red, and finally a uniform gold nanocluster solution was obtained. The molar ratio of chloroauric acid to sodium borohydride was 0.9:1.5.

[0101] (4) Centrifugation, washing, and drying: The gold nanocluster solution was transferred to a high-speed centrifuge tube, centrifuged at 8000 r / min for 20 minutes, and the bottom precipitate was collected. The precipitate was first ultrasonically dispersed and washed twice with 50 mL of anhydrous ethanol, each time for 10 minutes, followed by centrifugation. Then, it was ultrasonically dispersed and washed once with 25 mL of acetone, followed by centrifugation. The washed precipitate was transferred to a vacuum drying oven and dried at 55℃ and a vacuum of -0.095 MPa for 6 hours to obtain powdered gold nanocluster catalyst. TEM analysis showed that the average particle size of the catalyst was approximately 4 nm.

[0102] Example 1 Example 1 is performed according to the following steps.

[0103] I. Raw material pretreatment: (1) Hafnium tetrachloride drying: Hafnium tetrachloride was placed in a vacuum drying oven and dried for 3 hours at a temperature of 100℃ and a vacuum of -0.09MPa. After drying, a sample was taken and the moisture content was determined to be about 0.03wt% using a Karl Fischer moisture analyzer.

[0104] (2) Pretreatment of n-butyllithium solution: Place the n-butyllithium n-hexane solution in an anhydrous and oxygen-free glove box and let it stand for 30 minutes to remove any trace amounts of moisture and impurities that may be present.

[0105] (3) Organic solvent pretreatment: Place n-hexane in a distillation apparatus and collect the fraction at 69-70℃ by atmospheric distillation to remove trace impurities and moisture.

[0106] II. Reaction Process: In a 316L stainless steel reactor equipped with a jacket, mechanical agitator, and solid feed hopper, first evacuate to -0.08 MPa, then fill with high-purity nitrogen (99.999%) to a slightly positive pressure (0.01 MPa). Repeat this "evacuation-nitrogen filling" operation 4 times to ensure that air and moisture inside the reactor are completely removed.

[0107] (1) Preparation of dimethylaminolithium solution: Pretreated n-hexane was added to the reactor, and a low-temperature freezing liquid was introduced through the jacket to cool the system to about -78°C. The stirring speed was adjusted to 200 rpm, and dimethylamine and pretreated n-butyllithium solution were slowly added. The molar ratio of dimethylamine to n-butyllithium was controlled to be about 1:1, and the weight ratio of n-hexane to n-butyllithium was about 100:1. The reaction was carried out at -60°C for 8 hours until the reaction was complete, and dimethylaminolithium solution was obtained.

[0108] (2) Catalytic reaction: Under stirring, dried hafnium tetrachloride was slowly added to the dimethylaminolithium solution through a solid feed hopper, controlling the molar ratio of hafnium tetrachloride to dimethylaminolithium to be approximately 1:4.0. The system temperature was maintained at -78°C during the feeding process, and stirring was continued for 30 minutes after the feeding was completed. Subsequently, palladium-gold composite nanocluster catalyst 1 prepared in Preparation Example 1 was added, controlling the weight ratio of catalyst to hafnium tetrachloride to be approximately 0.005:1. The reactor was sealed, the stirring speed was adjusted to 350 rpm, and the system temperature was slowly raised through the jacket to control the temperature at -20°C. The reaction was stirred at this temperature for 4 hours to obtain a light yellow reaction solution. A small amount of white precipitate was observed to form during the reaction. In the catalytic reaction step (3), the catalytic reaction time was determined according to the reaction time determination method described in detail above.

[0109] III. Post-processing and purification: (1) Filtration and separation: After the reaction is completed, circulating cooling water is introduced through the jacket to cool the reaction liquid to 25°C. A pressure filtration device is used with a 0.22 μm filter membrane as the filter medium and filtration is carried out at a pressure of 0.4 MPa to separate the solid precipitate (lithium chloride and catalyst) and obtain a clear light yellow filtrate.

[0110] (2) Atmospheric distillation: Transfer the filtrate into an atmospheric distillation apparatus (18 theoretical plates). Under the protection of high-purity nitrogen, control the distillation temperature at 40°C and stop distilling when the volume of the distillate is 1 / 5 of the original volume. Remove most of the n-hexane and a small amount of low-boiling impurities.

[0111] (3) Vacuum distillation: The residue from atmospheric distillation is transferred to a vacuum distillation column (theoretical number of 35 plates), the vacuum degree is controlled at 0.1 kPa, the temperature of the distillation vessel is 80℃, the temperature of the top of the column is 82℃, and the reflux ratio is 0.5:1. Under these conditions, distillation is carried out for 5 hours, and the tetra(dimethylamino)hafnium main fraction is collected.

[0112] Based on the test methods described above for measuring yield, purity, chlorine impurity content and metal impurity content, the tetra(dimethylamino)hafnium product was characterized for performance, and data such as yield, purity, chlorine impurity content and metal impurity content were recorded. The results are shown in Table 4.

[0113] Example 2-12 Examples 2-12 were carried out in a similar manner to Example 1 to obtain tetra(dimethylamino)hafnium products, except that the formulation and process parameters were changed as shown in Table 3 below.

[0114] In the catalytic reaction step (3), the catalytic reaction time was determined according to the reaction time determination method described in detail above. In addition, the tetrakis(dimethylamino)hafnium products prepared in Examples 2-12 were characterized according to the test methods described in detail above for measuring yield, purity, chlorine impurity content and metal impurity content, and the data such as yield, purity, chlorine impurity content and metal impurity content were recorded. The results are shown in Table 4.

[0115] Comparative Example 1 Comparative Example 1 was performed in a similar manner to Example 1, except that the palladium-gold composite nanocluster catalyst 1 prepared in Preparation Example 1 was not added.

[0116] In the catalytic reaction step (3), the catalytic reaction time was determined according to the reaction time determination method described in detail above. In addition, the tetrakis(dimethylamino)hafnium product prepared in Comparative Example 1 was characterized according to the test methods described in detail above for measuring yield, purity, chlorine impurity content and metal impurity content, and the data such as yield, purity, chlorine impurity content and metal impurity content were recorded. The results are shown in Table 4.

[0117] Comparative Example 2 Comparative Example 2 was conducted in a manner similar to Example 1, except that the palladium-gold composite nanocluster catalyst 1 prepared in Preparation Example 1 was replaced with the palladium nanocluster catalyst prepared in Preparation Example 5.

[0118] In the catalytic reaction step (3), the catalytic reaction time was determined according to the reaction time determination method described in detail above. In addition, the tetrakis(dimethylamino)hafnium product prepared in Comparative Example 2 was characterized according to the test methods described in detail above for measuring yield, purity, chlorine impurity content and metal impurity content, and the data such as yield, purity, chlorine impurity content and metal impurity content were recorded. The results are shown in Table 4.

[0119] Comparative Example 3 Comparative Example 3 was conducted in a manner similar to Example 1, except that the palladium-gold composite nanocluster catalyst 1 prepared in Preparation Example 1 was replaced with the gold nanocluster catalyst prepared in Preparation Example 6.

[0120] In the catalytic reaction step (3), the catalytic reaction time was determined according to the reaction time determination method described in detail above. In addition, the tetrakis(dimethylamino)hafnium product prepared in Comparative Example 3 was characterized according to the test methods described in detail above for measuring yield, purity, chlorine impurity content and metal impurity content, and the data such as yield, purity, chlorine impurity content and metal impurity content were recorded. The results are shown in Table 4.

[0121] Table 3. Formulations and process parameters for Examples 1-12 and Comparative Examples 1-3

[0122] Table 4 Test results of Examples 1-12 and Comparative Examples 1-3

[0123] As can be seen from the results shown in Table 4 above, the tetra(dimethylamino)hafnium products prepared in Examples 1-12 of this invention exhibit good yield, purity, and Cl- content. - It exhibits significant advantages in both content and reaction time. Compared with Comparative Example 1, which did not use a catalyst, and Comparative Examples 2 and 3, which used single palladium nanocluster catalysts and gold nanocluster catalysts, it demonstrates the technical effect of introducing palladium-gold composite nanocluster catalysts in this invention.

[0124] Specifically, regarding reaction time, the catalytic reaction time of Examples 1-12 was controlled between 4.1 and 5.0 hours, with an average reaction time of only about 4.5 hours. Compared to Comparative Example 1 (28.9 hours) without a catalyst, the reaction time was shortened by more than 80%, significantly improving production efficiency and solving the core pain points of slow reaction kinetics and long production cycles in existing processes. Even compared to Comparative Example 2 (24.5 hours) and Comparative Example 3 (26.1 hours) using single palladium and gold nanoclusters catalysts, the reaction time of the embodiments of the present invention was shortened by 80%, indicating that the composite nanocluster structure formed by palladium and gold produced a significant synergistic catalytic effect. Its catalytic activity is far higher than that of single metal nanocluster catalysts, and it can effectively accelerate the ligand exchange reaction between hafnium tetrachloride and dimethylaminolithium.

[0125] Regarding product yield, the yields of Examples 1-12 all reached over 93%, with Example 12 achieving the highest yield of 98.3% and an average yield of approximately 95%. In contrast, the yield of Comparative Example 1 was only 72.8%, and the yields of Comparative Examples 2 and 3 were 83.5% and 81.2%, respectively, all below 90%. This difference indicates that the palladium-gold composite nanocluster catalyst of the present invention can significantly improve reaction selectivity, suppress the formation of impurities such as chlorinated byproducts, greatly improve product conversion and yield, and reduce raw material costs for industrial production.

[0126] Regarding product purity and impurity control, the tetra(dimethylamino)hafnium prepared in Examples 1-12 all achieved a purity of over 99.994%, with Example 12 reaching a purity of 99.999%. - The content of all samples was below 50 ppm, with the lowest being only 30 ppm, meeting the stringent requirements of advanced semiconductor manufacturing processes for electronic-grade precursors. Comparative Example 1, on the other hand, had a purity of 97.842%, Cl... - The content was as high as 185 ppm; the purities of Comparative Examples 2 and 3 were 98.696% and 98.853%, respectively, Cl - The content of all samples exceeded 89 ppm, failing to meet the standards for electronic applications. Furthermore, purity testing revealed that the total metal impurity content of the products in each embodiment was below 10 ppm, significantly better than the comparative example. This further demonstrates that the palladium-gold composite nanocluster catalyst exhibits good dispersibility, is not prone to detachment, and does not introduce additional metal impurities, thus balancing catalytic efficacy and product purity.

[0127] Meanwhile, the test results of Examples 1-12 also show that the product performance remains stable even when adjusting different organic solvents, raw material molar ratios, reaction temperatures, and catalyst types. This indicates that the process conditions according to the present invention have good adaptability and controllability, facilitating industrial scale-up. In summary, the present invention, by introducing a palladium-gold composite nanocluster catalyst with a specific structure, successfully solves the technical pain points of existing processes, such as long reaction time, low yield, and insufficient purity, achieving efficient and high-purity preparation of tetra(dimethylamino)hafnium, and possesses outstanding industrial application value.

[0128] Obviously, those skilled in the art can make various modifications and variations to this disclosure without departing from the spirit and scope of this disclosure. Therefore, if such modifications and variations fall within the scope of this invention, this disclosure is also intended to include such modifications and variations.

Claims

1. A method for preparing tetra(dimethylamino)hafnium from hafnium tetrachloride, characterized in that, The method includes the following steps: (1) Under anhydrous and oxygen-free conditions and inert gas protection, the organic solvent is cooled to -78°C to -40°C, dimethylamine and n-butyllithium are added, and the mixture is stirred to obtain a dimethylamine lithium solution, wherein the organic solvent is n-hexane, cyclohexane, toluene or a mixture thereof, and the molar ratio of dimethylamine to n-butyllithium is in the range of 1:1 to 1.2:

1. (2) Under anhydrous and oxygen-free conditions and inert gas protection, hafnium tetrachloride was added to the dimethylaminolithium solution, stirred evenly, and then palladium-gold composite nanocluster catalyst was added. The reaction temperature was controlled at -20℃ to 0℃, and the reaction was stirred for 4-5 hours to obtain a reaction solution. The molar ratio of hafnium tetrachloride to dimethylaminolithium was 1:4.0-1:4.5, and the weight ratio of palladium-gold composite nanocluster catalyst to hafnium tetrachloride was 0.005:1-0.05:

1. (3) Filter the reaction solution obtained in step (2) to remove the precipitate and obtain the filtrate; (4) The filtrate obtained in step (3) is subjected to atmospheric distillation to remove the organic solvent, and then the residue is subjected to vacuum distillation to obtain tetra(dimethylamino)hafnium, wherein: The palladium-gold composite nanocluster catalyst has an average particle size in the range of 3-12 nm, and The palladium-gold composite nanocluster catalyst was prepared by a method comprising the following steps: (a) Palladium chloride and chloroauric acid are dispersed in a mixed solvent of acetone and water to obtain a mixture, wherein the molar ratio of palladium chloride to chloroauric acid is in the range of 1:8 to 6:

8. (b) Add triphenylphosphine to the mixture obtained in step (a) and stir, wherein the ratio of the total number of moles of palladium chloride and chloroauric acid to the number of moles of triphenylphosphine is in the range of 1:1 to 1.2:1; (c) Under the protection of an inert gas, sodium borohydride aqueous solution is added dropwise to the mixture obtained in step (b), and the mixture is stirred at room temperature for 2-4 hours to obtain a palladium-gold composite nanocluster solution. (d) The palladium-gold composite nanocluster solution was centrifuged, washed, and vacuum dried to obtain the palladium-gold composite nanocluster catalyst.

2. The method according to claim 1, characterized in that, The weight ratio of the organic solvent to n-butyllithium is in the range of 100:1 to 200:

1.

3. The method according to claim 1, characterized in that, The n-butyllithium is added in the form of a n-butyllithium solution, which contains n-butyllithium and an organic solvent, wherein the organic solvent is n-hexane, cyclohexane, toluene, or a mixture thereof.

4. The method according to claim 1, characterized in that, The mixed solvent is a mixture of acetone and water in a volume ratio of 2:1 to 5:

1.

5. The method according to claim 1, characterized in that, The total molar ratio of palladium chloride and chloroauric acid to the added sodium borohydride is 0.6:1-1.2:

1.

6. The method according to claim 1, characterized in that, In step (a), the molar ratio of palladium chloride to chloroauric acid is in the range of 4:8 to 5:

8.

7. The method according to claim 1, characterized in that, The atmospheric distillation in step (4) is carried out under the protection of an inert gas, at a temperature of 40-80℃, and is stopped when the volume of the distillate is 1 / 5-1 / 3 of the original volume.

8. The method according to claim 1, characterized in that, The pressure of the vacuum distillation in step (4) is 0.1-1.0 kPa, the temperature of the distillation vessel is 80-120℃, the temperature of the top of the column is 82-95℃, and the reflux ratio is 0.5:1-3:1.

Citation Information

Patent Citations

  • Amino metal compound as well as preparation method and application thereof

    CN114195816A

  • Method for preparing organometallic compound

    WO2026106306A1